Impact of screen time on the mental health of adolescents in Bangladesh - Parves, Mohammad Masud; Kamrul M. Tanveer, Sharif; Hossain, M. Alamgir; Naser, A. Z. M.; Rahman, M. Mominur; Alam, Mohammad Rezwanur; Akter, Tuhin; Ahmed, Ehashan (International Journal Of Community Medicine And Public Health, 2024)
Background: The rapid increase in screen time among adolescents has raised concerns about its potential impact on mental health. This study aims to examine the relationship between screen time, sleep duration, and anxiety levels among school-going adolescents in Dhaka, Bangladesh. Methods: A cross-sectional observational study was conducted with 568 students from multiple schools in Dhaka, Bangladesh, specifically targeting Grades 9 and 10. Statistical analyses were performed using SPSS version 25, with Chi-square tests and ANOVA used to determine significance, set at p<0.05. Results: The study included 568 participants, with 60.2% female and 82.0% in Grade 10. The majority (54.9%) had a normal BMI, while 32.2% were underweight. Most participants (62.9%) reported getting 7-8 hours of sleep per day, with a mean sleep duration of 7.13 hours (SD=1.25). The mean screen time was 4.02 hours (SD=1.63), with 68.0% reporting 2-4 hours of screen use per day. Anxiety levels varied, with 54.2% reporting no anxiety symptoms, 35.9% mild anxiety, 7.0% moderate anxiety, and 2.8% severe anxiety. ANOVA results showed a significant association between screen time and anxiety levels (p=0.043), with severe anxiety corresponding to the highest mean screen time (5.01 hours). Conclusions: The study found significant associations between screen time, sleep duration, and anxiety levels among adolescents. These findings underscore the need for interventions promoting balanced screen use and adequate sleep to improve adolescent mental health. Further research is recommended to explore long-term effects and develop targeted interventions.